Antiulcer And Antioxidant Potential Of Zizyphus jujuba Mill Root Extract In Aspirin And Ethanol Induced Gastric Ulcers. - Sameena Alam; Md. Sajid Hussain; Madhavi K Reddy; M. V. Reddy; Rajesh Kumar Gupta (International Journal of Phytomedicine, 2016)
The root of Zizyphus jujuba Mill. (Rhamnaceae) (ZJ) has been used to treat mouth ulcers as indigenous medicine. However there is no scientific report of its use for protection and treatment of gastric ulcers. The aqueous root extract of ZJ (AREZJ) was evaluated for antiulcerogenic potential in aspirin and ethanol induced ulcer models in Wistar rats along with in vitro antioxidants potential. Single dose toxicity studies were carried out to determine LD50. Two doses i.e. 150 and 250 mg/kg b.wt were evaluated for antiulcer activity by measuring ulcer index and percentage of ulcer healing in two of the ulcer models. Antioxidants activity was estimated in vitro by DPPH, H2O2 free radical scavenging and reducing power assay. Phytocostituents were determined by standard method. Based on ulcer index, percentage protection of 76.92% in aspirin model and 70% in ethanol model were noted with a dose of 250 mg/kg b.wt of AREZJ, whereas standard drug omeprazol (50 mg/kg b.wt) showed 80.77 % and 80 % protection in aspirin and ethanol models respectively. AREZJ showed 89.2% DPPH and 88.5% H2O2 free radical scavenging activity at concentration of 200 μg/ml and 80 μg/ml respectively. AREZJ also exhibited 87.5% reducing power at 50 μg/ml. Phytochemical screening of AREZJ showed presence of alkaloids, carbohydrates, flavanoids, glycosides, proteins and tannins. No mortality was noted till 2500 mg/kg b.wt of AREZJ, indicating higher LD50 value. AREZJ was found to have antiulcerogenic effect, which could be related to its antioxidant potential.